Mitochondrial Genome of Spirometra theileri Compared with Other Spirometra Species - Ndosi, Barakaeli Abdieli; Park, Hansol; Lee, Dongmin; Choe, Seongjun; Kang, Yeseul; Nath, Tilak Chandra; Bia, Mohammed Mebarek; Eamudomkarn, Chatanun; Jeon, Hyeong-Kyu; Eom, Keeseon S. (Korean journal of parasitology, 2021)
This study was carried out to provide information on the taxonomic classification and analysis of mitochondrial genomes of Spirometra theileri. One strobila of S. theileri was collected from the intestine of an African leopard (Panthera pardus) in the Maswa Game Reserve, Tanzania. The complete mtDNA sequence of S. theileri was 13,685 bp encoding 36 genes including 12 protein genes, 22 tRNAs and 2 rRNAs with absence of atp8. Divergences of 12 protein-coding genes were as follow: 14.9% between S. theileri and S. erinaceieuropaei, 14.7% between S. theileri and S. decipiens, and 14.5% between S. theileri with S. ranarum. Divergences of 12 proteins of S. theileri and S. erinaceieuropaei ranged from 2.3% in cox1 to 15.7% in nad5, while S. theileri varied from S. decipiens and S. ranarum by 1.3% in cox1 to 15.7% in nad3. Phylogenetic relationship of S. theileri with eucestodes inferred using the maximum likelihood and Bayesian inferences exhibited identical tree topologies. A clade composed of S. decipiens and S. ranarum formed a sister species to S. erinaceieuropaei, and S. theileri formed a sister species to all species in this clade. Within the diphyllobothridean clade, Dibothriocephalus, Diphyllobothrium and Spirometra formed a monophyletic group, and sister genera were well supported.